Karakteritik Pasien Dan Kategori Gangguan Penglihatan Pra Operasi Dan Pasca Operasi Katarak Berbasis Komunitas Pusat Mata Nasional Rumah Sakit Mata Cicendo (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Introduction : The main causes of blindness in the world are cataract. Community-based cataract surgery plays an important role in reducing the burden of cataract blindness. Objective : To describe patient?s characteristic and visual impairment before and after community based cataract surgery. Methods : This is a retrospective descriptive study with secondary data from community-based cataract surgery by the Community Ophthalmology Installation of National Eye Center Cicendo Eye Hospital from January 2019 to December 2020. Visual impairment is divided into four categories based on WHO classification. Result : There were 3890 patients included. Most of patients were aged 60 to 69 years in 1533 people (39,41%). The most common diagnosis was immature senile cataract in 1826 people (46,94%). Most of patients underwent unilateral cataract surgery using Manual Small Incision Cataract Surgery method and implantation of intraocular lens. The most common category of visual impairment in one eye before surgery was blind, in 3714 eyes (95,48%) and one day after surgery was poor outcome, in 2466 eyes (63,39%). The two-eye blindness before surgery were 1492 people (38,35%) and after surgery were 652 people (16,76%). Sight restoration rate was 26,8%. Conclusion : Most of the patients were aged 60-69 years. The most common diagnosis is immature senile cataract. The category of one eye visual impairment before surgery was mostly blind, after surgery was moderate visual impairment. There number of blind patients was decrease from 38,35% before surgery to 16,76% after surgery.